Tinjauan Fatwa DSN-MUI Nomor. 04/DSN-MUI/IV/2000 dan PBI Nomor.07/46/PBI/2005 terhadap Akad Murabahah Bil Wakalah - Sekarini Teguh Pramesti; Nandang Ihwanudin; Iwan Permana (UNISBA Press, 2022)
Abstract. Murabahah Bil Wakalah contract is a multi-contract consiting of a Murabahah and Wakalah contract. According to the DSN-MUI Fatwa Number 05 of 2000 and PBI Number 07 of 2005, the Murabahah Bil Wakalah contract used in the Koperasi Mitra Dhuafa, acording to the DSN-MUI Fatwa Number 04 to 2000 and PBI Number 07 of 2995, should be that if the bank wants to represent (wakalah) to the costomer to buy goods, then the Murabahah contract must be carried out after the good are legally become the property of the Bank. In practice the Murabahah Bil Wakalah contract is carried out simultaneously. This study aims, fristly, to find out the implementation of the Murabahah Bil Wakalah contract at the Koperasi Mitra Dhuafa Majenang Branch, secondly to find out the riview of the DSN-MUI fatwa Number 04 of 2000 and PBI Number 07 of 2005 on the Murabahah Bil Wakalah contarct at the Koperasi Mitra Dhuafa Majenang Branch. The author uses a qualitative resaerch method with a case study reasearch approach. Types of field research data, primary and secondary data sources, data collection techniques with documentation observation and intervews. The results of this study are: first, the mechanism of the Murabahah Bil Wakalah contract is im accprdance with the DSN-MUI Fatwa Number 04 of 2000 and PBI Number 07 of 2005; second, the implemntation of the Murabahah Bil Wakalah contract is not in accordance wirh Fatwa point 9 and PBI ayat 1, because the Murabahah contract is carried out before the Wakalah contract in wich the sale and purchase of goods before becoming a bank principle, and proof of receipt is the end of the financing process, not the end of the Wakalah contract. Abstrak. Akad Murabahah Bil Wakalah merupakan multi akad yang terdiri dari akad Murabahah dan akad Wakalah. Akad Murabahah Bil Wakalah yang digunakan pada Koperasi Mitra Dhuafa, menurut Fatwa DSN-MUI Nomor 04 tahun 2000 dan PBI Nomor 07 Tahun 2005 yang seharusnya adalah jika bank hendak mewakilkan (wakalah) kepada nasabah untuk membeli barang, maka akad Murabahah harus dilakukan setelah barang secara prisnip menjadi milik Bank. Praktiknya akad Murabahah Bil Wakalah dilakukan secara bersamaan. Penelitian ini bertujuan, yang pertama, untuk mengetahui pelaksaan akad Murabahah Bil Wakalah di Koperasi Mitra Dhuafa Cabang Majenang, kedua untuk mengetahui tinjauan fatwa DSN-MUI Nomor 04 tahun 2000 dan PBI Nomor 07 Tahun 2005 pada akad Murabahah Bil Wakalah di Koperasi Mitra Dhuafa Cabang Majenang. Penulis menggunakan metode penelitian kualitatif dengan pendekatan penelitian studi kasus. Jenis data penelitian lapangan, sumber data primer dan sekunder, teknik pengumpulan data dengan dokumentasi, obeservasi dan wawancara.Hasil penelitian ini yaitu: Pertama, mekanisme akad Murabahah Bil Wakalah sesuai dengan Fatwa DSN-MUI Nomor 04 Tahun 2000 dan PBI Nomor 07 Tahun 2005; kedua, pelaksaan akad Murabahah Bil Wakalah tidak sesuai dengan Fatwa point 9 dan PBI ayat 1, karena akad Murabahah dilakukan sebelum akad Wakalah yang mana Jual beli barangnya sebelum menjadi prinsip bank, dan pembuktian kwitansi adalah akhir dari proses pembiayaan bukan akhir dari akad Wakalah.